PENERAPAN KEBIJAKAN PROGRAM DESA MANDIRI PBB-P2 DI KECAMATAN TAMBUSAI UTARA TAHUN 2018 - Andre Yulinusman; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Land and Building Tax ( PBB) is a type of local tax that is fully regulated by the goverment in determinating the amount of tax, this tax is important for the implwmwntation and improvment of devolopment as well as increasing the prosperity and welfare of the people, a problem that is always faced in term of rural and urban land and building taxes is colecction is not yet maximized due to tax data issued through the tax return form (SPPT), manu of which are not in accordance with the condition that should be to overcome these problems. The desa PBB-P2 program is a program compiled by the regional revenue agency of Rokan Hulu Regency wntrust of authority of the management and coleection of PBB-P2 tax to the village, starting from the taxpayer data collection, until the colecction of PBB-P2 tax to the community. This study aims to describe the implementation of the UN-P2 independent village program policy in the Tambusai Utara District, then also to find out the inhibiting factors for the non-optimal implementation of the independent village program policy in the Tambusai Utara District. The research location is in Rokan Hulu district, which is location in the regional revenue agency of Rokan Hulu regency and in Tambusai Utara sub-district, in the third bangun Jaya village, in mahato village, Furthermore, data collection techniques were carried out by interview and documentation. The result of study are the application of the UN-P2 independent village Program policy in Tambusai Utara District carried out by the regional revenue agency of Rokan Hulu regency that has not run optimally. This is caused by several faktor such as lack suppoting facilities and insfrastrukture in the village office, limited budget and lack of quantity of human resources. Keywords : Communication, Resources, Disposition, Bureaucratic Structure